2017
DOI: 10.5005/jp-journals-10036-1130
|View full text |Cite
|
Sign up to set email alerts
|

Spectrum of Microbial Isolates from Wound Infections in Patients admitted in a Tertiary Care Hospital, Kolkata

Abstract: Increasing emergence of drug-resistant bacteria is becoming a major problem globally. A retrospective study of 790 culture and sensitivity reports on microbial isolates, from infected wounds was carried out in KPC Medical College and Hospital, Jadavpur, Kolkata, India. 504 patients were males and 286 females. Gram negative organisms were isolated in 561 and gram positive in 229. Among the gram negative organisms, Klebsiella pneumoniae, Pseudomonas aeruginosa and Escherichia coli were the most common, whereas S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
2
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 16 publications
(27 reference statements)
2
2
0
Order By: Relevance
“…86 Antimicrobial resistance in E. coli has increased over the world. E. coli were resistant to tetracycline, cefotaxime, ciprooxacin, levooxacin and ceazidime about 100%, 100%, 86.7%, 86.7%, 73.3% respectively, however showed sensitivity to imipenem (93.3%), meropenem (80.0%), tigecycline (66.7%), cefoxitin (66.7%) and amikacin (60.0%) this results similar to previous studies reported by Saha et al, 87 and Yakha et al 88 Such studies stated that imipenem and amikacin are very effective drugs against E. coli isolates. In our study, the multidrug resistance ability within all identied bacteria was noticed.…”
Section: Antibiotics Inhibition Effectssupporting
confidence: 90%
“…86 Antimicrobial resistance in E. coli has increased over the world. E. coli were resistant to tetracycline, cefotaxime, ciprooxacin, levooxacin and ceazidime about 100%, 100%, 86.7%, 86.7%, 73.3% respectively, however showed sensitivity to imipenem (93.3%), meropenem (80.0%), tigecycline (66.7%), cefoxitin (66.7%) and amikacin (60.0%) this results similar to previous studies reported by Saha et al, 87 and Yakha et al 88 Such studies stated that imipenem and amikacin are very effective drugs against E. coli isolates. In our study, the multidrug resistance ability within all identied bacteria was noticed.…”
Section: Antibiotics Inhibition Effectssupporting
confidence: 90%
“…Escherichia coli isolates sensitivity against levofloxacin was found to be (92.3%) as shown in. Similar observations have been reported byYakha et al(2015);Gomatheswari andJeyamurugan (2017), andSaha et al(2017) that imipenem, amikacin, and gentamycin were very effective drugs against E. coli isolates but presented resistance against cefuroxime, ciprofloxacin, ofloxacin, cefotaxime, and ampicillin.…”
supporting
confidence: 88%
“…Hooper and Jacoby (2015) reported that resistance is due to changes in DNA gyrase enzyme and/or the topoisomerase enzymes or by the defective function of porine channels. Saha et al (2017) and Bhalchandra et al (2018) reported that P. aeruginosa strains were sensitive to levofloxacin, polymyxinb and ciprofloxacin and showed high resistance against ceftazidme and aztreonam. The diameters of the inhibition zones were interpreted according to CLSI ( 2016), The isolates were reported as R-resistant, I-intermediate and S-Sensitive.…”
Section: Resultsmentioning
confidence: 99%
“…This resistance is due to β-lactamase production (extended-spectrum beta lactamases) that hydrolyze these drugs (Palzkill, 2018). Earlier studies by Saha et al (2017) and Bhalchandra et al(2018) reported that P. aeruginosa strains were sensitive to polymyxinb, levofloxacin, and ciprofloxacin and showed high resistance against Aztreonam and ceftazidime. Yakha et al (2015) and Perimet al (2015) described high resistance against ceftazidime and polymyxin B.…”
Section: Discussionmentioning
confidence: 99%